Additions to the taxonomy of the Afrotropical Tetramorium weitzeckeri species complex (Hymenoptera, Formicidae, Myrmicinae), with the description of a new species from Kenya - Hita Garcia, Francisco; Fischer, Georg (European Journal of Taxonomy, 2014)
This study presents a taxonomic update of the Tetramorium weitzeckeri species group. Tetramorium mpala sp. nov. is described from Laikipia, Kenya, and placed in the T. weitzeckeri species complex. In addition, we also provide an illustrated identification key to the three species complexes of the T. weitzeckeri species group, and an updated illustrated identification key to species of this species complex.